Analisis Sistem Informasi Akuntansi Persediaan pada Minimarket New Sarana - Nurul Rizka Khoirunnisa; Zeni Rusmawati; Andrianto Andrianto (UMSurabaya Publishing, 2022)
An accounting information system is a computer-based system designed to convert accounting data into information. This information is useful to support the continuity of a business. Inventory is one of the most important components in accounting information systems because inventory is one of the assets that has a relatively large number of current assets or assets owned by the company. This research aims to determine the accounting information system for the inventory of merchandise at the â€œNew Saranaâ€ minimarket. This research is a descriptive qualitative research with research procedures in the form of observation, interviews, and documentation. Based on the results of the research, it is found that the service at the â€œNew Saranaâ€ minimarket is quite good. However, in the application of the accounting information system it still needed to be improved because many shortcomings could result in the different data of the amount of inventory physically and that listed on the computer. This is due to the existence of double jobs, incomplete documents, the lack of quality of human resources and the level of security, and the absence of Standard Operational Procedure (SOP) listed in the minimarket.Â